A web based health technology assessment in tele-echocardiography: the experience within an Italian project - Daniele Giansanti; Sandra Morelli; Giovanni Maccioni; Lorenzo Guerriero; Remo Bedini; Gennaro Pepe; Cesare Colombo; Gabriella Borghi; Velio Macellari (Istituto Superiore di Sanità, 2009)
Due to major advances in the information technology, telemedicine applications are ready for a widespread use. Nonetheless, to allow their diffusion in National Health care Systems (NHcSs) specific methodologies of health technology assessment (HTA) should be used to assess the standardization, the overall quality, the interoperability, the addressing to legal, economic and cost benefit aspects. One of the limits to the diffusion of the digital tele-echocardiography (T-E) applications in the NHcS lacking of a specific methodology for the HTA. In the present study, a solution offering a structured HTA of T-E products was designed. The methodology assured also the definition of standardized quality levels for the application. The first level represents the minimum level of acceptance; the other levels are accessory levels useful for a more accurate assessment of the product. The methodology showed to be useful to rationalize the process of standardization and has received a high degree of acceptance by the subjects involved in the study.